Landfilling of waste : (E & FN Spon, 1994)
In view of the great demand for information regarding landfills, a series of international reference books on landfilling of waste has been established. This book, the second volume, deals with lining and leachate collection. It consists of edited, selected contributions to the International Symposia on Sanitary Landfills held in Sardinia every second year.